The strategic narratives of decline and revival at London Transport, 1970 - 90 - James Fowler (Essays in Economic & Business History (EEBH), 2022)
This article argues that the historical stories of decline and revival in organisations are as important as the phenomenon itself. The complexity and humiliation of decline create strategic narratives which attempt to both clarify and justify events, but at the cost of over-simplification and exaggerating managerial agency. However, detailed business histories can embrace intricacy and account for the intrinsically political nature of managerial decision making. In this case study I propose that external politics drovestrategic "storytelling"designed to justify either profit-or utility-maximizing managerial choices as suitable reactions to decline in London's public transport. The article offers a new historical account of the management of decline and revival at London Transport between 1970-90 and explicitly links theories of organizational decline to political perspectives.
Keywords: H07; L02; L09; N07; R04; 330; Decline; Strategy; Narratives; Politics; London Transport